Determinan Struktur Modal Dengan Ukuran Perusahaan Sebagai Variabel Moderasi - Galuh Sukma Sasmita; Sri Wahyuni; Azmi Fitriati; Hardiyanto Wibowo (Jurnal Akademi Akuntansi, 2024)
Purpose: This research aims to analyze and test the influence of company growth, business risk, and asset structure on capital structure with company size as a moderating variable. Methodology/Approach: The population used in this research is tourism, restaurant and hotel sector companies that have been listed on the Indonesia Stock Exchange (BEI) in four periods, namely 2018-2021, totaling 31 companies. Findings: The results of this research explain that asset structure has a negative effect on capital structure, while company growth, business risk and company size have no effect on capital structure. Company size cannot moderate the influence of company growth, business risk, and asset structure on capital structure. Practical and Theroretical Contribution/Originality: This research contributes to investors, creditors, company management and researchers to increase understanding regarding the capital structure of tourism, restaurant and hotel sector companies. Capital structure as an independent variable can be used to monitor the company's funding conditions and as a consideration for investors and creditors in providing funding. A poor capital structure can increase financial risk to a company. Investors and creditors need to ensure that the company has an appropriate capital structure policy in handling financial obligations without facing high risks. Research Limitation: The independent variables used in this research were only able to explain 2.82% of the influence on capital structure. The remaining 71.8% is explained by other variables that are not in this study.